The burnt orange heresy - Willeford, Charles Ray, 1919-1988 (Overlook Press, 2020)
Fast-talking, backstabbing, womanizing, and fiercely ambitious art critic James Figueras will do anything--blackmail, burglary, and beyond--to make a name for himself. When an unscrupulous collector offers Figueras a career-making chance to interview Jacques Debierue, the greatest living--and most reclusive--artist, the critic must decide how far he will go to become the art-world celebrity he hungers to be. Will Figueras stop at the opportunity to skim some cream for himself or push beyond morality's limits to a bigger payoff?